ANALISIS PERAN DINAS TENAGA KERJA DAN TRANSMIGRASI DALAM PERLINDUNGAN TENAGA KERJA DI KOTA KENDARI - Suriyani BB; La Manguntara; Makmur Kambolong (Journal Publicuho, 2024)
This research aims to analyze and determine the role of the Manpower and Transmigration Service in Labor Protection in Kendari City and identify barriers to implementing the Labor Protection policy. This research adopted a qualitative descriptive research method and was conducted at the Kendari City Manpower and Transmigration Office. Informants in this research. The data used in this research involves information sourced from primary and secondary data. The data analysis technique used interactive data analysis according to Milles Hunerman and Saldana (2014). The research results show that the role of the Manpower and Transmigration Service in Kendari City in protecting workers includes aspects of law, safety, health, social security and work relations. Even though efforts have been made such as providing fair wages, preventing work injuries, routine health checks, financial protection, and protecting the right to organize, there are still obstacles to policy implementation such as ineffective communication and limited resources that affect policy implementation.